English language teaching practices and implementations in higher education: Systematical literature review - Mihret, Getachew; Joshi, Jagdish S (Teaching English as a Foreign Language Journal, 2024)
According to English language teaching (ELT) practices and implementations, the problem-solving approach that puts students at the center of learning should serve as the foundation for the teaching and learning processes. As a result, it was determined that the principles and methods of communicative language teaching should serve as the foundation for English language instruction in higher education. Additionally, it was asserted that employing communicative language teaching methods will raise students' level of English language competency. Consequently, the goal of this methodically examined literature was to evaluate the methods and applications of English language instruction in the system of higher education. The investigator collected previously published works from the Scopus database. He reviewed articles published between the years 2016 and 2024. The researcher carried out six steps to direct the review: a systematic literature review utilizing the PRISMA approach (Mihret et al., 2024). The researcher kept 24 papers out of 139 that were carefully examined. Key words employed by the researcher were English language teaching and teaching, as well as higher education. The items could be retrieved on May 28, 2024. The final papers were used by the researcher instead of articles that were being considered for publishing in press, and the language used to publish those articles was English. The social sciences and the arts and humanities were the subject areas he employed most frequently. The results showed that in practices and implementations of English language teaching in higher education system, some problems such as, learner-related factors, teacher- related factors, socio-cultural influences, time and physical constraints, and shortage of materials are occurred.